The Protohermes guangxiensis species-group (Megaloptera: Corydalidae), with descriptions of four new species - Liu, Xingyue; Hayashi, Fumio; Yang, Ding (Zootaxa, 2008)
The Protohermes guangxiensis group (Megaloptera: Corydalidae) is proposed for five species from eastern and southeastern Asia. Four species are described as new to science: Protohermes furcatus sp. nov., Protohermes impunctatus sp. nov., Protohermes piaoacanus sp. nov., and Protohermes zhuae sp. nov. A key is provided for males of the species.